2022
DOI: 10.1002/cbdv.202200376
|View full text |Cite
|
Sign up to set email alerts
|

Six New Polyoxygenated Xanthones from Garcinia cowa and Their Neuroprotective Effects on Glutamate‐Mediated Hippocampal Neuronal HT22 Cell Death

Abstract: Six new polyoxygenated xanthones, garcicowanones F -H (1-3), norcowanol A -B (4-5), and garcinone F (6) along with twelve known compounds 7-18 were obtained from the latex of Garcinia cowa Roxb. ex Choisy. All new compounds have a 1,3,7-trioxygenated or 1,3,6,7-tetraoxygenated xanthone nucleus and differ from majority of xanthones from G. cowa by hydrated side chains. Compounds 1, 7, 8 and 18 exhibited significant neuroprotective effects on glutamate-mediated hippocampal neuronal HT22 cell death. In particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In light of the previously reported studies, the current study reported the neuroprotective potential of chamuangone-rich extract (Sae-Lim et al, 2020). Chamuangone-rich extract has remarkable potential to reduce and prohibit free radical production in HT22 cells (Nguyen et al, 2022). The lipid membranes of the brain are very vulnerable to lipid peroxidation and are key characteristics in the development of neurodegenerative disorders, such as PD and Alzheimer's disease (Singh et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In light of the previously reported studies, the current study reported the neuroprotective potential of chamuangone-rich extract (Sae-Lim et al, 2020). Chamuangone-rich extract has remarkable potential to reduce and prohibit free radical production in HT22 cells (Nguyen et al, 2022). The lipid membranes of the brain are very vulnerable to lipid peroxidation and are key characteristics in the development of neurodegenerative disorders, such as PD and Alzheimer's disease (Singh et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…Its major phytoconstituents are flavonoids, xanthones, phloroglucinols, chamuangone, cowaxanthone, and garcicowanone (Paudel et al, 2022;Ritthiwigrom et al, 2013). Recent studies have suggested the robust antioxidant and neuroprotective potential of polyoxygenated xanthones and garcicowanone through the mechanism of reducing Ca +2 influx and by prohibiting the synthesis of reactive oxygen species (ROS; Nguyen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These findings underscore the significance of melatonin as a potential neuroprotective agent with promising implications for the management of neurodegenerative diseases. In a similar vein, in 59 the neuroprotective potential of Garcinia cowa extracts against glutamate‐mediated hippocampal neuronal HT22 cell death was explored. The study showed six novel polyoxygenated xanthones from the extracts, with garcicowanone F showing remarkable neuroprotective activity, promoting more than 80% cell viability in a concentration‐dependent manner.…”
Section: Implications For Excitotoxicity and Neuroprotection In Cns D...mentioning
confidence: 99%